2017
DOI: 10.1002/pd.5172
|View full text |Cite
|
Sign up to set email alerts
|

Parental experiences of prenatal whole exome sequencing (WES) in cases of ultrasound diagnosed fetal structural anomaly

Abstract: Parents desired as much information as possible and appreciated information being repeated and provided in various formats. Many struggled with clinical uncertainty relating to the cause and prognosis following a fetal anomaly diagnosis and found it difficult to balance the risks of invasive testing against their need for more definitive information. Parents trusted their clinicians and valued their support with decisions in pregnancy. Testing was sometimes pursued to reassure parents that their baby was "norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 20 publications
1
52
0
Order By: Relevance
“…The health professionals described that parents ‘want a good thing to come out of a bad situation’ (MW4) and ‘be able to contribute in some way to the development of knowledge’ (MW3). The desire for more information which the professionals we interviewed reported as the main drive for parents’ participation in PAGE, was confirmed also by a study exploring the experiences of parents who took part in the PAGE project [ 20 ].…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The health professionals described that parents ‘want a good thing to come out of a bad situation’ (MW4) and ‘be able to contribute in some way to the development of knowledge’ (MW3). The desire for more information which the professionals we interviewed reported as the main drive for parents’ participation in PAGE, was confirmed also by a study exploring the experiences of parents who took part in the PAGE project [ 20 ].…”
Section: Resultsmentioning
confidence: 74%
“…A study exploring parents’ experiences within PAGE [ 20 ] confirmed that the long turnaround time in the study was difficult for some of the parents recruited.…”
Section: Resultsmentioning
confidence: 99%
“…In a qualitative study assessing parental experiences following whole exome sequencing for fetal abnormalities, parents expressed already feeling fear and anxiety over the uncertainty and prognosis following the detection of an ultrasound anomaly and pursued exome sequencing due to a desire for information. Participants had exome sequencing under the PAGE research study in the UK, which only disclosed pathogenic variants (Quinlan-Jones et al 2017). Thus, no studies have specifically examined counseling for VUS results returned from clinical reports.…”
Section: Discussionmentioning
confidence: 99%
“…Further, even in the context of ostensibly valid consent, data suggest that women may not appreciate in advance the effect that uncertain results have on their well‐being, sense of identity, or relationship to their pregnancy and/or child . In a qualitative study, prospective parents indicated that having clear information about expected results from prenatal WES is extremely important …”
Section: Discussionmentioning
confidence: 99%
“…20 In a qualitative study, prospective parents indicated that having clear information about expected results from prenatal WES is extremely important. 21 Some have argued that advance discussions about the potential for results to introduce "pivotal decisions about ending or continuing their pregnancy" are an "ethical responsibility." 19 Such discussions may need to take into account concerns of disability rights advocates that "prenatal tests to select against disabling traits express a harmful attitude about and send a hurtful message to people who live with these traits."…”
Section: Challenge and Recommendations: Adequate Counseling And Infmentioning
confidence: 99%